Pengaruh Penggunaan Smartphone Pascapandemi Terhadap Motivasi Belajar IPA Siswa Kelas IX SMPN 6 Tangerang Selatan - Nuri Rimbawati; Hamdani Hamdani (Departement of Mathematics Education, 2023)
This research aims to determine the effect of post-pandemic smartphone use on students' science learning motivation to find a solution to minimize excessive smartphone use. This type of quantitative research is a survey method with sampling using simple random sampling techniques. Data collection techniques use interview instruments, questionnaires, and documentation. Data analysis techniques using descriptive statistics, prerequisite tests, and hypothesis testing. The results of the research are that the gender frequency is 50.6 male and 49.4 female. The results of a simple linear regression of variable X against Y were obtained namely the Sig value. 0.002 < 0.05, and the calculated t value is 3.207 > t table 1.994 and, the contribution size is 11.5%. The conclusion is that the smartphone use variable influences the science learning motivation variable and there are solutions to minimize excessive smartphone use.